Osmium isotopic homogeneity in the CK carbonaceous chondrites. (1st November 2017) - Goderis, Steven; Brandon, Alan D.; Mayer, Bernhard; Humayun, Munir
Abstract: Variable proportions of isotopically diverse presolar components are known to account for nucleosynthetic isotopic anomalies for a variety of elements (e.g., Ca, Ti, Cr, Ni, Sr, Zr, Mo, Ru, Pd, Ba, Nd, and Sm) in both bulk chondrites and achondrites. However, although large Os isotopic anomalies have been measured in acid leachates and residues of unequilibrated chondrites, bulk chondrites of various groups, iron meteorites, and pallasites exhibit Os isotopic compositions that are indistinguishable from terrestrial or bulk solar isotopic abundances. Since the magnitude of nucleosynthetic anomalies is typically largest in the carbonaceous chondrites, this study reports high-precision Os isotopic compositions and highly siderophile element (HSE) concentrations for ten CK chondrites. The isotope dilution concentration data for HSE and high-precision Os isotope ratios were determined on the same digestion aliquots, to precisely correct for radiogenic contributions to 186 Os and 187 Os. While acid leached bulk unequilibrated carbonaceous chondrites show deficits of s-process Os components to the same extent as revealed by unequilibrated enstatite, ordinary, and Rumuruti chondrites, equilibrated bulk CK chondrites exhibit no resolvable Os isotopic anomalies. These observations support the idea that acid-resistant, carbon-rich presolar grains, such as silicon carbide (SiC) or graphite, are major carriers for nucleosynthetic isotopic anomalies of Os. The destruction of these presolar grains, which are omnipresent in unequilibrated meteorites, must have occurred during aqueous alteration and thermal metamorphism, early in the CK chondrite parent body history. The dispersal of CK chondrites along the IIIAB iron meteorite isochron on a 187 Os/ 188 Os versus 187 Re/ 188 Os diagram, with Re/Os ratios from 0.032 to 0.083, in combination with the observed redistribution of other HSE (e.g., Pt, Pd), highlights the influence of parent body processes, overprinted by effects of recent terrestrial alteration. Under the oxidizing conditions prevalent on the CK parent body, evident from high abundances of magnetite and limited Fe-Ni metal in CK chondrites, these parent body processes made all isotopically anomalous Os, originally hosted in reduced presolar grains, accessible. The absence of Os isotopic anomalies in ordinary, enstatite, and now also carbonaceous chondrites, implies that the carriers of s- and r-process Os must have been effectively homogenized across the region of chondrite formation, and possibly even the entire solar protoplanetary nebula, as suggested by the Os isotopic compositions of iron meteorites and non-anomalous ureilites. Except for a limited number of ureilites, the relative proportions of presolar s- and r-process carriers of Os (and other elements such as W) in chondrites, and most other planetary bodies, must have remained constant during all subsequent nebular and planetary processes, which appears not to have been the case for other siderophile elements, including Mo, Ru, and Pd. The existence of Mo, Ru, Pd and other siderophile element isotopic anomalies thus appears to be in part controlled by the chemical properties of these elements (e.g., volatility), their host phase(s) (e.g., SiC, graphite, metal, sulfides), and the nature of the nebular or planetary processes experienced in the early solar system.